Joel's Revolutionary Table: New York and Mexico City in Turbulent Times. (2nd October 2017) - Hulme, Peter
ABSTRACT: The network considered here consisted of a journalist and a cartoonist based in New York and a young Mexican artist, respectively Benjamin De Casseres, Carlo de Fornaro, and Marius de Zayas. They worked together in 1906 on a newspaper in Mexico City, forging a friendship based on their opposition to the corrupt and dying regime of Porfirio Díaz. Back in New York the network survived, at least in the short term, while De Casseres and de Zayas defended and supported their friend Fornaro as he was prosecuted by Díaz's cronies with the connivance of the US state.